Fluorine-containing block/branched polyamphiphiles forming bioinspired complexes with biopolymers - Paiuk, Olena; Mitina, Nataliya; Slouf, Miroslav; Pavlova, Ewa; Finiuk, Nataliya; Kinash, Nataliya; Karkhut, Andriy; Manko, Nazar; Gromovoy, Taras; Hevus, Orest; Shermolovich, Yuriy; Stoika, Rostyslav; et al. (Colloids and surfaces. B, Biointerfaces, 2019)
Colloidal-chemical characteristics of block/branched cationic and non-ionic polyamphiphiles containing poly(fluorine-alkyl methacrylate) (poly(FMA)) block and their intermolecular complexes with biopolymers were studied. The dependences of their surface activity and micelle size on the length of hydrophobic and hydrophilic blocks, as well as the length of side fluorine-alkyl branches were established. Poly(FMA)-block-poly(DMAEMA) was used for formation of interpolyelectrolyte complexes with plasmid DNA (pDNA) via their electrostatic interaction. Novel non-viral polyplexes were tested as gene delivery systems for mammalian cells. The results of DLS, TEM and MALDI-ToF studies demonstrated disaggregation of lysozyme (LYZ) aggregates in the presence of poly(FMA)-block-poly(NVP) and formation of the polyamphiphile…LYS complex possessing antibacterial action.
Keywords: Plasmids; methakryláty; muramidasa; Muramidase; Micelles; DNA; plazmidy; Polyethylene Glycols; hydrofobní a hydrofilní interakce; polyethylenglykoly; Methacrylates; Hydrophobic and Hydrophilic Interactions; Polymers; zvířata; polymery; Animals; Fluorine; technika přenosu genů; Gene Transfer Techniques; micely; fluor